EXPLORATION OF THE USE OF PHET SIMULATION ON NEWTON'S LAW MATERIALS TO IMPROVE STUDENT PHYSICS LEARNING OUTCOMES - Siregar, Juliandi; Mawaddah, Hajar; Khairiah, Khairiah; Berliani, Halimah; Nasution, Lia Afriyanti; Putri, Nur Amelia; Derlina, Derlina; Pramudito, Rafaza; Ehkan, Phaklen (Universitas Labuhanbatu, 2024)
AbstractThe background to this research is that physics lessons are often considered difficult and less interesting by students, especially because of their abstract nature, the complexity of mathematical calculations, and the difficulty in connecting theory with practice. One of the challenging topics is Newton's Law of motion, which includes the relationship between force, mass and acceleration. This research was carried out at MA Muallimin UNIVA Medan, by applying the Problem Based Learning (PBL) learning model, an innovative learning media that is relevant to development. technology. This research utilizes PHET (Physics Education Technology), an interactive simulation platform developed by the University of Colorado Boulder, to support learning Newton's Laws. PHET allows students to carry out virtual experiments independently with various variables, such as mass, force and surface type, so that student learning outcomes increase. The research method used is quantitative in class X-G. The instrument used is a written test (essay) with a total of 10 questions. It is known that the pretest and posttest data are normally distributed with a significance value of Pretest (0), Posttest (0,), and are declared homogeneous with a significance value Based on Mean (0.245) where the normality and homogeneity test values exceed (>) the real level used in the measurement namely α = 0.05 or 5%. With the help of SPSS, it is known that the average posttest student learning outcomes (85.93) are higher than the pretest (58.80), so it can be concluded that the hypothesis is accepted.